(untitled) (Journal of Asian Development Studies, 2025)
Emotional intelligence is found to be an essential part of personal and institutional success, and it has been examined through many models and studies Nicolae (2023). However, there is a dearth of knowledge about precise and appropriate models that should be used to develop emotional intelligence capabilities in higher education students. To respond effectively to this century’s dynamic environment, today’s competitive environment has always pushed for hiring personnel in institutions that possess academic and emotional intelligence skills. It is proposed that by integrating different approaches and strategies into their curriculum, universities might contribute significantly to the growth of EI. A review of the development of emotional intelligence is consistent with opportunities for development in the university students’ setting. The findings show that the ability model is the best EI model for academic settings, and the Goleman EI Model is best for measuring the performance of employees (teachers) in given areas. Bar-On model is a "superior predictor of human performance" in both workplace and academia. Today’s students are tomorrow’s employees, so higher education should take steps to prepare students according to market needs. Recommendations for implementing EI in higher education are discussed.